2011
DOI: 10.1007/s12525-011-0051-5
|View full text |Cite
|
Sign up to set email alerts
|

Co-authorship networks in electronic markets research

Abstract: This article examines co-authorship networks of researchers publishing in Electronic Markets-The International Journal of Networked Business (EM). The authors visualize the co-authorship network and provide descriptive statistics regarding the degree to which researchers are embedded in the co-authorship network. They develop and test seven hypotheses associating the researchers' embeddedness in the co-authorship network with the number of the researchers' citations. Results indicate that author who publish co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 74 publications
3
34
0
1
Order By: Relevance
“…Finally, the results of H4 show that centrality values clearly affect the number of citations. This is exactly in line with the results of studies by [74,98], which confirmed a positive correlation between centrality values and citation values.…”
Section: Discussionsupporting
confidence: 91%
“…Finally, the results of H4 show that centrality values clearly affect the number of citations. This is exactly in line with the results of studies by [74,98], which confirmed a positive correlation between centrality values and citation values.…”
Section: Discussionsupporting
confidence: 91%
“…At the micro level (node or actor level), the most widely statistic used to describe the co-authorship network is an author's degree centrality (Fischbach et al, 2011), which reflects the number of collaborators of researchers. In other words, degree centrality measures how many connections tie authors to their immediate neighbours in the network (i.e.…”
Section: --Insert Figure 3--mentioning
confidence: 99%
“…Indeed, co-citation analysis would allow for a better appraisal of knowledge flow among academic papers and specialties (i.e., the cross-pollination of ideas across knowledge domains) (Ciotti et al, 2016, Nerur et al, 2015. Further, this analysis would help in estimating the impact of how authors' embeddedness in research communities affects their research in terms of impact (see Collet et al, 2014, Fischbach et al, 2011 Another possible line of future research is to examine co-authorship networks by means of an improved mixed-method approach (i.e., combining qualitative and quantitative methods to enrich the explanation of underlying processes and their meaning to the actors involved). This would avoid an overemphasis on the structural dimension of social networks at the expense of the relational contents (see Kase et al, 2013), and assist in finding answers to questions regarding processes and factors that explain co-authorship (Velden and Lagoze, 2013;Velden et al 2010;Fry and Talja, 2007).…”
Section: Limitations and Suggestions For Future Researchmentioning
confidence: 99%
“…Quanto mais pontos estão ligados uns aos outros, mais denso será o gráfico. No contexto de uma rede de coautoria, a densidade reflete o percentual do total da rede com o qual um ator foi coautor de um artigo (FISCHBACH;PUTZKE;SCHODER, 2011).…”
Section: Análise De Redes Sociaisunclassified